FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL PERFORMANCE PERUSAHAAN MANUFAKTUR - Anggaraeni, Adelia Sekar Sri; Setijaningsih, Herlin Tundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to prove the effect of leverage, firm size, and sales growth on financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. Sampling method used in this research is the purposive sampling method by finding 67 samples of manufacturing companies. This research was conducted by testing hypotheses on each variable that had been determined by performing multiple regression of panel data using the E-Views 12 software. The results found from this study indicate that leverage and sales growth have a significant and positive influence on financial performance. However, firm size have a positive non-significant effect on financial performance.